2021
DOI: 10.4103/jfmpc.jfmpc_2419_20
|View full text |Cite
|
Sign up to set email alerts
|

Oral pain and infection control strategies for treating children and adolescents in India

Abstract: Introduction: Oral and dental health form an integral part of complete well being of an individual and society at large. Promoting oral health and societal progression go hand in hand. Aim: To investigate dentists' attitudes about pain and infection control while treating children and adolescents by assessing their recommendations of pre- and postoperative analgesics and antibiotics, and use of local anesthesia (LA) for definitive treatment in different clinical scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Twenty-six studies [ 32 , 33 , 34 , 35 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ] explored the indications and reasons for antibiotic prescription/dispensing. Of these, 25 studies involved questionnaire surveys of dentists, and one study [ 38 ] involved antibiotic dispensing by pharmacists without a prescription to patients with dental complaints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six studies [ 32 , 33 , 34 , 35 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ] explored the indications and reasons for antibiotic prescription/dispensing. Of these, 25 studies involved questionnaire surveys of dentists, and one study [ 38 ] involved antibiotic dispensing by pharmacists without a prescription to patients with dental complaints.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, twenty studies [ 32 , 33 , 34 , 35 , 56 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 83 , 85 , 86 , 87 , 89 ] assessed therapeutic and prophylactic indications for antibiotic use in dentistry.…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed the overuse of antibiotics and analgesics, particularly in the postoperative phase, by general dentists rather than specialists, for pain control and treatment of infections, even in children and adolescents [65].…”
Section: Thompson 2022mentioning
confidence: 95%
“…Clinical situations requiring antibiotic therapy on an empiric basis are limited to and include oral infections associated with signs of systemic spread of infection [17,65], such as elevated body temperature, lymphadenopathy, and lockjaw [13]. Coherently, antibiotics are not indicated for all odontogenic infections and should not be used in place of eliminating the cause of infection [72].…”
Section: Antibiotic Therapy In Dentistry: Current Measuresmentioning
confidence: 99%